The Pengaruh Model Pembelajaran Case Based Learning Berbantuan Ar terhadap Hasil Belajar dan Keterampilan Proses Sains Siswa di SMA Negeri 13 Samarinda: - - Parung, Yasthin; Herliani, Herliani; Maasawet, Elsje Theodora; Rambitan, Vandalita Maria Magdalena (PendIPA Journal of Science Education, 2024)
Current education advances pupils to actively participate in the learning process. The Industry 4.0 revolution affects education 4.0, which involves the use of digital technology, or cyber system, in the learning process. With the application of such technology enables learning to take place unlimited space and time, meaning learning processes not only in the classroom and at the time of learning hours. This study aimed to determine the effect of Case Base Learning model assisted by Augmented Reality media on learning outcomes and science process skills on the material of the reproductive system of students in class XI SMA Negeri 13 Samarinda. The type of research used by researchers was quasy experiment with the research design, namely the one group pretest-posttest design. The results of data analysis obtained were the average student pretest score is 50.13 and the posttest is 87.26 the N-gain value is 0.74 with a high category. This, it is stated that there is an effect of the case base learning model on learning outcomes and science process skills of class XI students of SMA Negeri 13 Samarinda.